ChemInform Abstract: Tin‐Mediated One‐Pot Synthesis of α, α‐Disubstituted Homoallylic Hydrazides from Ketones, Acylhydrazines and Allyl Bromide. Issue 23 (May 2016) - Lu, Ailing; Huang, Danfeng; Wang, Ke‐Hu; Su, Yingpeng; Ma, Junyan; Xu, Yanli; Hu, Yulai
Abstract: The reaction works well with a variety of cyclic and acyclic ketones though 1‐tetralone and benzophenone do not give the desired products.